Penetapan Harga Jual Produk Murabahah Studi Kasus di BMT Rama Salatiga - Annisa, Arna Asna (IAIN Salatiga, 2013)
This thesis is entitled Selling Price Regulation of Murabahah Product Case Study: BMT RAMA Salatiga. The objectives of this research are to describe 1) the execution of murabahah transaction at BMT RAMA Salatiga, 2) the method in deciding and applying the selling price of murabahah product, and 3) the policy of BMT on conducting its business based on Islamic principles. This research applied descriptive qualitative design and was conducted based on normative-juridical approach. The subjects of the research were the manager of BMT RAMA Salatiga and the costumers of BMT RAMA who were involved in murabahah transactions. The results show that the execution of murabahah transaction has not been applied well. Basically, wakalah aqad should place the costumer as the representative of BMT to get goods before the aqad is signed. It is applied in order to prevent gharar and to draw a distinction between syariah and conventional banking. In regulating its funding product BMT RAMA considers some components such as risks of fund, cost of fund, operational cost, annual profit target, annual funding target, and competition rates. However, the cost of fund component has the consequence of interests which need to be considered in determining murabahah margin. This consequence is absolutely inapropriate with MUI instruction no. 1 year 2004, which forbids interests because of its belonging to riba. Unfortunately, the DPS assistance is still insufficient on this matter.